2018
DOI: 10.1097/sla.0000000000002040
|View full text |Cite
|
Sign up to set email alerts
|

Lauren Histologic Type Is the Most Important Factor Associated With Pattern of Recurrence Following Resection of Gastric Adenocarcinoma

Abstract: In GA patients who recur after resection, patterns of recurrence vary significantly based on Lauren histologic type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 32 publications
4
102
1
1
Order By: Relevance
“…However, few studies related to PRS have been reported. Lee conducted a followup of 386 patients with postoperative recurrence of GC, revealing a median survival of 8.4 months after recurrence and a close correlation between the Lauren classification and PRS [49]. The current study demonstrated that preoperative HCP is associated with DM, LN and LR.…”
Section: Discussionsupporting
confidence: 58%
“…However, few studies related to PRS have been reported. Lee conducted a followup of 386 patients with postoperative recurrence of GC, revealing a median survival of 8.4 months after recurrence and a close correlation between the Lauren classification and PRS [49]. The current study demonstrated that preoperative HCP is associated with DM, LN and LR.…”
Section: Discussionsupporting
confidence: 58%
“…Gastric cancer (GC) is the fifth most common malignancy in humans and ranks third in tumor-related mortality [1]. Although scholars have worked hard to improve the diagnosis and treatment of gastric cancer, the recurrence rate of patients with gastric cancer is still high-approximately 18-45.5% [2][3][4]-and the long-term survival rates are still not optimal [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse‐type gastric cancer cells are discohesive and can easily be separated from the primary tumor site. A recent study of 957 gastric cancer cases found diffuse type as a significant factor for peritoneal recurrence . They also showed that high pT category was significantly associated with peritoneal recurrence.…”
Section: Discussionmentioning
confidence: 95%